2019
DOI: 10.3390/rs11232854
|View full text |Cite
|
Sign up to set email alerts
|

Sequential InSAR Time Series Deformation Monitoring of Land Subsidence and Rebound in Xi’an, China

Abstract: Interferometric synthetic aperture radar (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…9. This is distinct from a rebound area in Xi'an introduced in [40]. Instead, IC1 mapped the spatial range of rebound deformation in Yuhuazhai, well south and west of Xi'an.…”
Section: B Spatiotemporal Deformation Pattern Analysismentioning
confidence: 89%
See 2 more Smart Citations
“…9. This is distinct from a rebound area in Xi'an introduced in [40]. Instead, IC1 mapped the spatial range of rebound deformation in Yuhuazhai, well south and west of Xi'an.…”
Section: B Spatiotemporal Deformation Pattern Analysismentioning
confidence: 89%
“…Large-scale InSAR data have been used to investigate the spatiotemporal characteristics of subsidence and ground fissures in Xi'an. These include global positioning system and InSAR observations from 2005 to 2006 [44]: Envisat, ALOS, and Ter-raSAR SAR datasets from 2005 to 2012 [45]; ERS, Envisat, and Sentinel SAR datasets from 2003 to 2017 [46]; ALOS, TerraSAR, and Sentinel SAR datasets from 2012 to 2018 [47]; and Sentinel SAR datasets from 2015 to 2019 [40]. These studies showed that degradation of the aquifer system had led to complex subsidence and ground fissures.…”
Section: A Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The subway line usually passes through the central area with large population and dense buildings. The excavation of subway tunnel will also change the original equilibrium of the stratum (including rock-soil layer and aquifer), resulting in varied degrees of ground subsidence [4], [5]. The subsidence causes two kinds of safety problems.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of orthogonal triaxial-stress experiments with CH 4 seepage, a complete stress-strain relationship and the corresponding evolution of volumetric strain and permeability were obtained. Wang et al [14] investigated the effect of pore-fluid pressure on normal deformation by laboratory experiments. Experiment results indicated that pore-fluid pressure significantly affects the normal deformation of a jointed sample.…”
Section: Introductionmentioning
confidence: 99%